2016
DOI: 10.14814/phy2.12867
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic systolic heart failure on lung structure-function relationships in large airways

Abstract: Heart failure (HF) is often associated with pulmonary congestion, reduced lung function, abnormal gas exchange, and dyspnea. We tested whether pulmonary congestion is associated with expanded vascular beds or an actual increase in extravascular lung water (EVLW) and how airway caliber is affected in stable HF. Subsequently we assessed the influence of an inhaled short acting beta agonist (SABA). Thirty‐one HF (7F; age, 62 ± 11 years; ht. 175 ± 9 cm; wt. 91 ± 17 kg; LVEF, 28 ± 15%) and 29 controls (11F; age; 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…One study in dogs using CT scanning found approximately a 20% reduction in airway area with saline infusion [32]. A previous study in our lab found small reductions in the luminal airway of the large airways after fluid loading, but no differences in large airways in patients with HF [15, 33]. These divergent findings confound the understanding of the relationship between pulmonary function and thoracic blood volumes that were found in this study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…One study in dogs using CT scanning found approximately a 20% reduction in airway area with saline infusion [32]. A previous study in our lab found small reductions in the luminal airway of the large airways after fluid loading, but no differences in large airways in patients with HF [15, 33]. These divergent findings confound the understanding of the relationship between pulmonary function and thoracic blood volumes that were found in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…A histogram technique to semi-quantitatively measure differences in EVLW was used [23, 33, 36]. A decreased skew and kurtosis and increased FWHM as found here suggest the presence of additional EVLW in stable, chronic patients with HF compared with control subjects.…”
Section: Discussionmentioning
confidence: 85%
“…12,14 Following treatment, spirometric measures were greatly improved but remained lower than those of chronic, stable patients observed in our laboratory. 8,14 Additionally, DLCO and Vc did not change, but Dm and Dm/Vc ratio improved. These changes were paralleled by clearance of EVLW, suggesting the pulmonary congestion present at admission was at least partially cleared by hospital discharge.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously demonstrated increased levels of extravascular lung water (EVLW) associated with decreased pulmonary function in chronic, stable HF patients. 8 In these patients, there is decreased pulmonary function, including forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC), and forced expiratory flow at 25-75% of FVC (FEF ); decreased diffusing capacity for carbon monoxide (DLCO); and altered gas exchange at both rest and exercise. [9][10][11] However, the degree to which these functional variables may be modified by therapeutic intervention during an acute decompensation and recovery during a course of inpatient treatment has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that CT derived measures of large airway wall thickness and luminal area are not different in healthy control subjects relative to stable HFrEF patients (27). In combination with the findings of the present study, data from our laboratory suggest that stable, well compensated HFrEF patients have evidence of elevated lung fluid volume but not substantial large airway edema and/or engorgement relative to their healthy age and sex matched counterparts.…”
Section: Discussionmentioning
confidence: 99%